AB0075 AICAR Induced Mitochondrial Apoptosis and Inhibited Cell Proliferation and MMP-3/RANKL Secretion via Enhancement of Mitochondrial Biogenesis in Rheumatoid Arthritis Fibroblast-Like Synovial Cells. (15th July 2016) - Ueha, T.; Sakai, Y.; Maeda, T.; Morishita, M.; Fukuda, K.; Hayashi, S.; Nishimoto, H.; Miura, Y.; Kuroda, R.; Hashiramoto, A.; Kurosaka, M.
Abstract : Background: Joint destruction in rheumatoid arthritis (RA) progresses via the hyperproliferation of the synovium and secretion of MMP-3/RANKL from fibroblast-like synoviocytes (FLS). [1] In tumors, we previously reported that the expression of mitochondrial biogenesis-related genes is low and increased numbers of mitochondria enhance cell apoptosis. [2] However, the relationship between mitochondrial biogenesis and cell apoptosis in RA-FLS remains unclear. Objectives: This research was investigated the relationship between mitochondrial biogenesis and cell apoptosis in RA-FLS. Methods: RA and Osteoarthritis (OA)-FLS were obtained during total knee replacement surgery from patients with RA. All experiments were conducted using cells from passages 3–7. Quantitative PCR was used to assess the expression of mitochondria-related mRNA (PGC-1α, NRF-1, and TFAM) and number of mitochondrial DNA (mtDNA) in RA- and OA-FLS with/without 5-aminoimidazole-4-carboxamide riboside (AICAR) (2 mM). Apoptosis was evaluated immunoblot analysis for cleaved caspase-3, -8, -9, and PARP 48 hours after an AICAR treatment in RA-FLS. Cell viability was assessed using WST-8 assay, and MMP-3/RANKL secretion was measured using an immunoassay (immunoblot and ELISA) with/without IL-1β or TNFα stimulation in RA-FLS. Inhibitory experiments were used AMPK inhibitor (20 μM Compound C) and mitochondrial biogenesis- inhibitor (10 μM TFAM-siRNA) by Lipofectamine® RNAiMAX Reagent in RA-FLS. Results: The expression of NRF-1 and TFAM and the levels of mtDNA were lower in RA-FLS than in OA-FLS. In RA-FLS, the levels of mtDNA and mRNA expression of mitochondria-related genes were enhanced by AICAR. Additionally, AICAR enhanced mitochondrial apoptosis (Increased the protein of cleaved caspase-3, -9, and PARP), and Treatment with an AMPK inhibitor (compound C) and a mitochondrial biogenesis- inhibitor (TFAM-siRNA) suppressed the inhibitory effect of AICAR on apoptosis. Moreover, AICAR inhibited cell viability and IL-1β- or TNFα-induced MMP-3/RANKL secretion in inflammation-induced RA-FLS. Conclusions: Mitochondrial biogenesis in RA-FLS was down-regulation. Enhancement of mitochondrial biogenesis resulted in the suppression of disease activities of RA, such as increasing mitochondrial apoptosis and reducing RA-FLS viability and secretion of MMP-3/RANKL from RA-FLS. A novel therapeutic approach by changing mitochondrial biogenesis is proposed. References: Bottini N, Firestein GS, Duality of fibroblast-like synoviocytes in RA: passive responders and imprinted aggressors. Nat Rev Rheumatol. 2013 Onishi Y, Ueha T, Kawamoto T, et al, Regulation of mitochondrial proliferation by PGC-1α induces cellular apoptosis in musculoskeletal malignancies. Sci Rep. 2014 Acknowledgement: The authors wish to express sincere thanks to Ms. Kyoko Tanaka, Ms. Maya Yasuda, and Ms. Minako Nagata (Department ofOrthopaedic Surgery, Kobe University Graduate School of Medicine) for their technical assistance. Disclosure of Interest: None declared